Motivasi, Kerjasama dan Keterlibatan: Pengaruhnya Terhadap Kinerja Karyawan CV. Indo Jaya Putra Surabaya - Sugijanto, Sugijanto; Handoko, Yunus; Kusdyah Rachmawati, Ike (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This research was conducted at CV. Indo Jaya Putra Surabaya which aims to find out and analyze: 1) the direct influence of motivation on employee performance, 2) the direct influence of collaboration on employee performance, 3) the direct influence of employee involvement on employee performance, and 4) the direct influence of motivation , employee cooperation and involvement on employee performance. This type of research is a quantitative method with a questionnaire to collect data, the saturated sample or total sampling is a population of all 53 employees from various operational departments at CV. Indo Jaya Putra Surabaya. Using multiple linear regression analysis using SPSS version 25. The results of this research show: 1) Work Motivation has no significant effect on Employee Performance, 2) Collaboration has a significant effect on Employee Performance, 3) Employee Engagement has a significant effect on Employee Performance, and 4) Work Motivation, Cooperation and Employee Involvement simultaneously have an effect significant impact on CV employee performance. Indo Jaya Putra, Surabaya.